A Performance Test of a Power Index Computer Program - Pajala Antti (Turun yliopiston politiikan tutkimuksen laitos, 2022)
There is a considerable literature studying voting power and power indices, however a
study exploring the practical aspects of voting power computation seems missing. This
study examines a power index program termination time and runtime memory usage in
large voting bodies up to 190 voters. In a comparison an up-to-date computer
surprisingly performs overwhelmingly better compared to a slightly older model. The
simulations reveal the greater speed of the up-to-date computer being due to more
advanced processor architecture together with a more efficient data bus and memory.
The applied all-in-one program is found rather slow due to simultaneous processing of
many indices. The runtime memory usage is found modest in the simulations. The
literature suggests that the time and storage complexity of the applied algorithm could
be reduced.